Comprehensive RNA-sequencing analysis in serum and muscle reveals novel small RNA signatures with biomarker potential for DMD - Coenen-Stass, AML; Sork, H; Gatto, S; Godfrey, C; Bhomra, A; Krjutškov, K; Hart, JR; Westholm, JO; O'Donovan, L; Roos, A; Lochmüller, H; Puri, PL; et al. (Elsevier, 2018)
Extracellular small RNAs (sRNAs), including microRNAs (miRNAs), are promising biomarkers for diseases such as Duchenne muscular dystrophy (DMD), although their biological relevance is largely unknown. To investigate the relationship between intracellular and extracellular sRNA levels on a global scale, we performed sRNA sequencing in four muscle types and serum from wild-type, dystrophic mdx, and mdx mice in which dystrophin protein expression was restored by exon skipping. Differentially abundant sRNAs were identified in serum (mapping to miRNA, small nuclear RNA [snRNA], and PIWI-interacting RNA [piRNA] loci). One novel candidate biomarker, miR-483, was increased in both mdx serum and muscle, and also elevated in DMD patient sera. Dystrophin restoration induced global shifts in miRNA (including miR-483) and snRNA-fragment abundance toward wild-type levels. Specific serum piRNA-like sRNAs also responded to exon skipping therapy. Absolute miRNA expression in muscle was positively correlated with abundance in the circulation, although multiple highly expressed miRNAs in muscle were not elevated in mdx serum, suggesting that both passive and selective release mechanisms contribute to serum miRNA levels. In conclusion, this study has revealed new insights into the sRNA biology of dystrophin deficiency and identified novel DMD biomarkers.